The Article The Role of Parents in Supporting the Education of Their Children in the Digital Age in Indonesia: The Role of Parents in Supporting the Education of Their Children in the Digital Age in Indonesia - Bayu Febrian Al-Farabi Raden family; Farhan Ihromi Lubis; Nursapia Harahap; Jordi Fahrezy; Nazma Ainina; Shafira Putri Zharifa (Yayasan Al'Adzkiya Rantauprapat, 2024)
The rapid development of digital technology has brought about significant changes in the world of education, including in Indonesia. The digital age provides new opportunities and challenges for children in their learning process. Therefore, the role of parents in supporting children's education in this digital era becomes very important. This study aims to explore the role of parents in supporting children's education in the digital era in Indonesia. The research method used is a qualitative approach by conducting in-depth interviews. The findings show that parents play an important role in supporting children's education in the digital era, including facilitating access to digital technology, providing guidance, being role models, and collaborating with schools. This research contributes to the understanding of the role of parents in supporting children's education in the digital age in Indonesia, and can provide insights for stakeholders to develop relevant programmes or policies.